The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14061523
|View full text |Cite
|
Sign up to set email alerts
|

Development of Toughened Flax Fiber Reinforced Composites. Modification of Poly(lactic acid)/Poly(butylene adipate-co-terephthalate) Blends by Reactive Extrusion Process

Abstract: The presented study focuses on the development of flax fiber (FF) reinforced composites prepared with the use of poly(lactic acid)/poly(butylene adipate-co-terephthalate)—PLA/PBAT blend system. This type of modification was aimed to increase impact properties of PLA-based composites, which are usually characterized by high brittleness. The PLA/PBAT blends preparation was carried out using melt blending technique, while part of the samples was prepared by reactive extrusion process with the addition of chain ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…A Teflon ® sheet was applied in between the polymer and the hot plate during this operation to avoid the adhesion of the film to the plate. The average areal fibres density used in the prepregs was 250 ± 20 g/m 2 [21][22][23][24].…”
Section: Bamboo Fibre Prepreg Preparationmentioning
confidence: 99%
“…A Teflon ® sheet was applied in between the polymer and the hot plate during this operation to avoid the adhesion of the film to the plate. The average areal fibres density used in the prepregs was 250 ± 20 g/m 2 [21][22][23][24].…”
Section: Bamboo Fibre Prepreg Preparationmentioning
confidence: 99%
“…Interestingly, the addition of reactive compatibilizers also improves the fiber-matrix interface interactions for composites [33,34], especially for materials with the addition of the lignocellulosic fillers [35,36]. Our previous research on PLA/PBAT systems aimed to indicate the improvement of wettability of flax fibers with the addition of CE [37]. Due to hydroxyl groups presence on the surface of the natural fibers, it is possible to obtain a permanent connection with CE epoxy groups.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in this area confirmed that PLA-based composites are able to withstand prolonged exposure to high temperatures. However, the investigated samples were usually prepared by compression molding or annealing [ 83 , 84 ].…”
Section: Resultsmentioning
confidence: 99%